Prothymosin alpha and its mimetic hexapeptide improve delayed tissue plasminogen activator‐induced brain damage following cerebral ischemia. Issue 6 (10th October 2019) - Halder, Sebok Kumar; Matsunaga, Hayato; Ueda, Hiroshi
Abstract: Tissue plasminogen activator (tPA) administration beyond 4.5 h of stroke symptoms is beneficial for patients but has an increased risk of cerebral hemorrhage. Thus, increasing the therapeutic window of tPA is important for stroke recovery. We previously showed that prothymosin alpha (ProTα) or its mimetic hexapeptide (P6Q) has anti‐ischemic activity. Here, we examined the beneficial effects of ProTα or P6Q against delayed tPA‐induced brain damage following middle cerebral artery occlusion (MCAO) or photochemically induced thrombosis in mice. Brain hemorrhage was observed by tPA administration during reperfusion at 4.5 and 6 h after MCAO. Co‐administration of ProTα with tPA at 4.5 h inhibited hemorrhage and motor dysfunction 2–4 days, but not 7 days after MCAO. ProTα administration at 2 and 4.5 h after MCAO significantly inhibited tPA (4.5 h)‐induced motor dysfunction and death more than 7 days. Administration of tPA caused the loss of tight junction proteins, zona occulden‐1 and occludin, and up‐regulation of matrix metalloproteinase‐2/9, in a ProTα‐reversible manner. P6Q administration abolished tPA (4.5 h)‐induced hemorrhage and reversed tPA (6 h)‐induced vascular damage and matrix metalloproteinase‐2 and 9 up‐regulation. Twice administrations of P6Q at 2 h alone and 6 h with tPA significantly improved motor dysfunction more than 7 days. In photochemically induced thrombosis ischemia, similar vascular leakage and neuronal damage (infarction and motor dysfunction) by late tPA (4.5 or 6 h) were also inhibited by P6Q. Thus, these studies suggest that co‐administration with ProTα or P6Q would be beneficial to inhibit delayed tPA‐induced hemorrhagic mechanisms in acute ischemic stroke. Abstract : Administration of tissue plasminogen activator (tPA) beyond 4.5 h increases the risk of cerebral hemorrhage. Here, tPA administration during reperfusion at 4.5 or 6 h after middle cerebral artery occlusion or photochemically induced thrombosis in mice caused brain damage with hemorrhage. Co‐administration of prothymosin α (ProTα) or its mimetic hexapeptide (P6Q) inhibited tPA‐induced such brain damage. Therefore, ProTα or P6Q co‐administration would be beneficial to inhibit tPA‐induced hemorrhagic mechanisms in ischemic stroke.